ANALISIS PATHLOSS JARINGAN 5G MIDDLE BAND 3,5GHZ DENGAN MODEL STANFORD UNIVERSITY INTERIM (SUI) DAN CLOSE-IN (CI) - Karangan, Nazario (Universitas Lampung, 2025)
The implementation of 5G networks in Indonesia continues to develop, with a primary focus on achieving equitable coverage through the construction of adequate infrastructure. This development is influenced by several technical parameters, such as gNodeB height, distance, and transmit power, all of which directly affect network performance, including the value of pathloss. Pathloss refers to the reduction in power or loss of energy during the transmission of information through radio waves, which is influenced by factors such as distance, frequency, and antenna height. By considering these aspects, the deployment of 5G networks is expected to provide optimal benefits for both operators and users, particularly in ensuring reliable services in urban areas. This study analyzes pathloss and received power at a frequency of 3.5 GHz (mid-band) with distance as the main parameter, using a comparison of 5G pathloss models for urban macro cells, namely the Stanford University Interim (SUI) model and the Close-In (CI) model. The modeling process was carried out through simulations using Matlab R2021a software. The results show that distance significantly affects both pathloss and received power in both models (SUI and CI). The greater the distance between the gNodeB and the receiver, the higher the pathloss value, under both Line of Sight (LOS) and Non-Line of Sight (NLOS) conditions. In the CI model under LOS conditions, the lowest pathloss value obtained was 101.48 dB, while the highest value in the SUI model was 140.45 dB. A similar pattern was observed under NLOS conditions, where the lowest pathloss value was recorded in the CI model at 125.63 dB, while the highest value was found in the SUI model at 150.45 dB.